2017
DOI: 10.3892/mco.2017.1500
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal osteosarcoma of the lung following treatment of primary small‑cell lung carcinoma with chemoradiotherapy: A case report

Abstract: Abstract. Primary pulmonary osteosarcoma is a rare entity, with only a few cases reported in the literature to date. Moreover, secondary extraskeletal osteosarcoma of the lung following chemoradiotherapy is extremely rare and, to the best of our knowledge, this is the first reported case. We herein present the case of an 80-year-old male patient with small-cell lung cancer (SCLC), who developed what it was initially considered as recurrence of the tumor after chemoradiotherapy. The patient eventually succumbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition, a slow-growing bone phenotype would be under strong negative selective pressure to emerge compared with rapidly growing SCLC, and therefore this should be an extremely uncommon event. There are rare case reports of patients developing carcinoids with ossification (Tsubochi et al 2013;Özsȩn et al 2020) and extraskeletal osteosarcoma (ESOS) in the lung (Qian et al 2017), including one ESOS following chemotherapy treatment of SCLC (Takamura et al 2018), but these could represent secondary tumors. Given that ASCL1 repression of SOX9 is conserved, however, it is tempting to speculate that treatments that block ASCL1 potently in the clinic could push tumor evolution to a dedifferentiated NC stem-like state.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a slow-growing bone phenotype would be under strong negative selective pressure to emerge compared with rapidly growing SCLC, and therefore this should be an extremely uncommon event. There are rare case reports of patients developing carcinoids with ossification (Tsubochi et al 2013;Özsȩn et al 2020) and extraskeletal osteosarcoma (ESOS) in the lung (Qian et al 2017), including one ESOS following chemotherapy treatment of SCLC (Takamura et al 2018), but these could represent secondary tumors. Given that ASCL1 repression of SOX9 is conserved, however, it is tempting to speculate that treatments that block ASCL1 potently in the clinic could push tumor evolution to a dedifferentiated NC stem-like state.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no confirmed etiology for the disease has been found, and radiation therapy administered near the lesion’s location and trauma may contribute to primary intrapulmonary osteosarcoma’s development ( 1 ). Takamura et al ( 23 ) reported a case of extraosseous osteosarcoma secondary to chemoradiotherapy in the lung. But in this case, there was no history of such treatment in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…A slow-growing bone phenotype would be under strong negative selective pressure compared to rapidly-growing SCLC, and therefore likely to be an extremely rare event. However, there are rare case reports of patients developing carcinoids with ossification 58,59 and extraskeletal osteosarcoma (ESOS) in the lung 60 , including one ESOS following chemotherapy treatment of SCLC 61 . It is tempting to speculate that treatments that block ASCL1 potently in the clinic, could push tumor evolution to a bone-like fate, or more likely, to a faster-growing dedifferentiated MSC or NC stem cell-like state.…”
Section: Discussionmentioning
confidence: 99%